ORGANIZATIONS WHICH PROVIDE CONSULTATIVE SERVICES IN SERBIA - Branko Mihailović; Drago Cvijanović (Ekonomika Poljoprivrede (1979), 2018)
In West Europe countries, the consultative services had developed for decades backwards, so today are active numerous consultative organizations which differ one from another by organization, financing model and process of consulting. However, the consultative services market in Serbia is very atypical, with massive number of small consultative organizations and extremely small number of big companies. Taking into consideration other well defined markets, the consultative market is susceptible to continuous changes, which is normal regarding specificity of businesses they do, and emergency to research permanently new forms of organization and to be ahead of a practice.